Label-Free Detection of Ochratoxin A Using Aptamer as Recognition Probe at Liquid Crystal-Aqueous Interface - Devi, Manisha; A, Kavyasree; Pani, Ipsita; Sil, Soma; Pal, Santanu Kumar (Frontiers in Soft Matter, 2022)
Aqueous interfaces of stimuli-responsive, thermotropic nematic liquid crystals (LC) have been utilized in the design of biosensing platforms for a range of analytes. Owing to the orientational changes in LC, these interfaces can easily report aptamer-target binding events at the LC-aqueous interface. We demonstrate a robust and label-free method for the detection of Ochratoxin A (OTA) using aptamer as the recognition probe. The self-assembly of CTAB (cetyltrimethylammonium bromide; cationic surfactant) at the aqueous-LC interface gives a homeotropic orientation of LC. In presence of negatively charged OTA specific aptamer, aptamer forms a complex with CTAB. Formation of aptamer-CTAB complex results in ordering transition of LCs to planar/tilted. In presence of OTA, OTA forms strong and stable G-quadruplex structure of aptamer that results in the redistribution of CTAB at LC-aqueous interface and leads to homeotropic orientation of LC. The designed LC aptasensor exhibits a detection limit of 0.1 nM. We observed that the sensitivity of LC aptasensor was affected by the pH and ionic strength. In addition, we demonstrated the applicability of the designed LC aptasensor for the detection of OTA in tap water and apple juice. This approach offers advantages over the conventional detection methods in terms of fabrication, ease of operation and analysis.